(untitled) (Patan Prospective Journal, 2024)
The article investigates the connection between sexuality, repression, and power. This study explores how power influences sexuality, forming specific discourses, while also examining how sexuality produces power. The scholar applies Foucauldian discourse in interpreting Toni Morrison’s novel Sula in order to examine sexuality and repression. It also explores the impact of power and sexuality within the Bottom community and the behaviors of the characters. In this book, there are characters that battle for the cause of justice. The novel has a repressive theme illustrating the conflicts of its characters. The woman utilizes sexual behavior to assert power and challenge male dominance. The way the characters engage in sexual activities reflects the society they are a part of. It provides insight into the African American community’s struggle against racism and sexism. In this manner, power influences everything just as it shapes the novel. The research paper has been written based on both primary and secondary materials from both electronic and print sources. The writing is analytical and critical in terms of theme discussion and theory application. Since the research has been based on the qualitative research design, the dialogues among the characters of the novel have been the basis of analysis.